2007
DOI: 10.1002/j.2161-1882.2007.tb00017.x
|View full text |Cite
|
Sign up to set email alerts
|

The Academic Rational Beliefs Scale: Development, Validation, and Implications for College Counselors

Abstract: This study reports on a new instrument, the Academic Rational Beliefs Scale, designed to measure college students' academic beliefs along a rational-irrational continuum. The new instrument is potentially useful when working with students experiencing academic difficulties. Information about test construction, reliability, validity, and generalizability are presented and implications, benefits, and cautions associated with use of the instrument as a college counseling tool are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…These newer measures should not be overshadowed by more commonly used tests which have less sound psychometric qualities. Finally, the theories of Ellis and Beck have been applied more recently to specific problems involving irrational thought; while these scales were not included in this review for reasons noted earlier, we find the Academic Rational Beliefs Scale [58], the Gambler's Beliefs Questionnaire [93], and the Irrational Food Beliefs Scale [94] to possess excellent psychometric properties and should be more widely used when assessing context specific problems involving irrational beliefs.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These newer measures should not be overshadowed by more commonly used tests which have less sound psychometric qualities. Finally, the theories of Ellis and Beck have been applied more recently to specific problems involving irrational thought; while these scales were not included in this review for reasons noted earlier, we find the Academic Rational Beliefs Scale [58], the Gambler's Beliefs Questionnaire [93], and the Irrational Food Beliefs Scale [94] to possess excellent psychometric properties and should be more widely used when assessing context specific problems involving irrational beliefs.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Maltby and Day [56] found one factor in a non-clinical population resulting in one composite score; while addition research [57] found a significant correlation between IBS scores and a depressive attributional style. The IBS was not initially named by Watson et al [53]; Day and Maltby [57] referred to it as the Irrational Beliefs Survey, while Egan, Canale, del Rosario, and White [58] referred to it as the Irrational Beliefs Scale.…”
Section: Measures Based On the Ellis Modelmentioning
confidence: 99%
“…In the university context, there are existing scales for the measurement of university students. For example, Egan, Canale, del Rosario, and White () have developed the Academic Rational Beliefs Scale, a specific measure of the trait for evaluating academic beliefs among university students along a rational–irrational continuum. Western culture is quite different from Chinese culture and the statements or items of this scale are unlikely to give the whole picture of a Chinese student's thoughts due to several reasons.…”
Section: The Measurement Of Irrational Beliefsmentioning
confidence: 99%
“…Ειδικότερα ως προς τον καρκίνο του μαστού, ως και ένα τρίτο των γυναικών που πάσχουν μπορεί να εμφανίζουν ψυχολογική νοσηρότητα κατά τη διάρκεια του έτους που ακολουθεί την αρχική επέμβαση (Lloyd-Williams et al, 2001, Thewes et al, 2004. Είναι γνωστό ότι οι παρενέργειες των συστηματικών θεραπειών του καρκίνου μπορεί επίσης να παίξουν ένα ρόλο στην ψυχολογική προσαρμογή (Ferrell et al, 1996, Institute of Medicine 2006, με προβλήματα που μπορεί να επιμένουν σε ένα σημαντικό ποσοστό γυναικών για πολλά χρόνια μετά τις θεραπείες (Stanton et al, 2002, Knobf 2002.Επιπλέον πολλές ψυχοκοινωνικές και δημογραφικές μεταβλητές έχει αναγνωριστεί ότι επηρεάζουν την ψυχολογική νοσηρότητα, όπως π.χ η ηλικία της ασθενούς κατά τη διάγνωση (Cowley et al,2000, Arora et al, 2001, η οικογενειακή κατάσταση , τα προβλήματα υγείας μετά την επέμβαση που δεν σχετίζονται με τον καρκίνο ή είναι απότοκα των θεραπειών , Glaus 2006, τα γεγονότα ζωής (Peled et al, 2007) και τα χαρακτηριστικά της προνοσηρής προσωπικότητας , White et al,2007, Giese-Davies 2008.…”
Section: σεξουαλικότηταunclassified
“…Ιrrational Beliefs Survey/ Scale: I.B.S) H κλίμακα παράλογων πεποιθήσεων (I.B.S)(Watson et al,1990) είναι ένα ψυχομετρικό εργαλείο 11 λημμάτων που χρησιμοποιεί απλουστευμένη γλώσσα.Ο Watson και οι συνεργάτες του αρχικά δεν έδωσαν όνομα στο ερωτηματολόγιο.Οι Day και Maltby (Day andMaltby, 2003) αναφέρθηκαν σε αυτό ως ψυχομετρικό εργαλείο Έρευνας Παράλογων Πεποιθήσεων (Irrational Beliefs Survey), ενώ οι Egan, Canale, del Rosario και White(Egan et al, 2007) χρησιμοποίησαν το ίδιο εργαλείο ονομάζοντάς το Κλίμακα Παράλογων Πεποιθήσεων (Irrational Beliefs Scale) . Αποτελεί την μετεξέλιξη μιας προηγούμενης αρχικής μορφής μιας κλίμακας μέτρησης των παράλογων πεποιθήσεων(McDonald and Games, 1972).…”
unclassified